(untitled) (Pedagogical Horizons, 2025)
The Digital Navigator project is presented as a case study that tests practical and everyday approaches to promoting democracy-related skills such as source criticism, perspective shifting and reflective media use in the digital space. The aim is to strengthen pupils’ critical judgement and sensitise them to dealing with disinformation, framing, AI-generated content and digital forms of violence. To this end, gamification and simulation-based learning settings are used that tie in with the lives of young people. The evaluation follows a formative assessment and is based on 56 workshops with 852 participants, as well as standardised feedback questionnaires and structured observations during the workshops. The feedback shows a high level of acceptance of the methods, with 91% of participants rating the offerings as interesting, interactive and helpful. Playful formats that enabled motivation and a change of perspective proved particularly effective, as did co-creation, which allowed students to take responsibility and promoted participatory skills. Challenges arose from the heterogeneity of prior experiences and gender-specific differences in participation. The results show that playful and dialogical approaches provide helpful impulses for knowledge acquisition, reflective skills and democracy-related sub-skills, thus opening up good transfer potential for schools, youth work and media education practice.